Analysis of daily energy expenditure of elite athletes in relation to their sport, the measurement method and energy requirement norms - Fraczek, B.; Grzelak, A.; Klimek, A. T. (Journal of Human Kinetics, 2019)
The purpose of this study was to estimate the daily energy expenditure (DEE) of 30 Polish elite athletes (15 women and 15 men aged 20 to 34 years) representing aerobic-endurance sports and speed-strength sports and to compare the obtained values with energy requirement norms recommended for athletes. Participants` DEE was measured for seven days using a chronometric-tabular method and a kinematic method. The kinematic method provided significantly lower values of DEE, by 25%. Mean DEEs obtained for female aerobic-endurance and speed-strength athletes were 3042.6 ± 389 and 3255.7 ± 359 kcal/24h (a chronometric-tabular method) and 2230.9 ± 209 and 2346.3 ± 355 (the kinematic method), respectively. The differences between the two groups were not statistically significant (p > 0.05). Male athletes` mean DEEs were significantly higher (p < 0.05): 3778.0 ± 657 and 4036.7 ± 532 kcal/24h (a chronometric-tabular method) for aerobic-endurance athletes and 2983.3 ± 545 and 2970.4 ± 345 (the kinematic analysis) for speed-strength athletes. As in the case of female athletes, the differences were not significant (p > 0.05). While no evidence was found that the type of sport alone could cause significant differences in the overall mean DEE between aerobic endurance athletes and speed-strength athletes, athletes` sex significantly differentiated women from men in that respect (the latter`s DEE was significantly greater). Such differences were not noted, though, when athletes` relative DEE (adjusted for body mass and body composition) were compared. The study revealed that the actual energy requirements of individual athletes can vary in a wide range and that they can be different from recommended energy intake.